Comparing diagnostic PET versus response PET at the 16th week induction and it’s correlation with MFC MRD: a deeper look into myeloma genomics - Ray, Vedanta; Goswami, Uddiptya; Sarvanen, Mages; Ananthakrishnan, Ramya; Jayaraman, Kumanan; Thirumalairaj, Raja (International Journal of Research in Medical Sciences, 2025)
Background: Multiple Myeloma is a heterogenous disease. A homogenous approach to a heterogeneous disease is discouraged as more and more data evolves. Diagnostic PET is recorded for measuring the disease burden along with metabolic uptake of the burden. Minimal residual disease (MRD) measurement at the end of induction, consolidation and pre-maintenance have been looked into by multiple authors. Also, follow-up PET is done at multiple time points by multiple authors and has been correlated with molecular response. In this study, we shall correlate PET response post 16 weeks of induction and MRD assay. Methods: We have a retrospective analysis of the newly diagnosed multiple Myeloma (NDMM) with all the baseline data available at our centre and received the standard induction regimen for 16 weeks and the follow-up data was analyzed. Results: At the end of the 16th week of induction, 41 patients were in complete resolution in PET. Of them, 26 had MRD detected and 15 had no MRD detected. Ten patients had stable disease, with all of them positive for MRD. One patient with positive MRD was having a partial response. Four patients with detectable MRD had progressive disease on PET, with (p=0.058). Conclusions: MRD should be correlated with follow-up FDG PET/CT for a comprehensive evaluation of treatment response. We firmly believe that the genome of the disease drives the disease and definitely, MRD-PET correlation should be attributed to genomics.